The impact of financial restatements on financial markets: A systematic review of the literature - Fragoso, J. L. F. R. (2020)
Purpose: The purpose of this paper is to discuss the most relevant issues related to the impact of financial restatements in the dynamics of financial markets and identify several research gaps to be investigated in future research. Design/methodology/approach: The methodology is based on a systematic review of the literature described by Tranfield et al. (2003). The final sample includes 47 academic papers published from 1996 to 2019. Findings: Papers in this domain discuss three main topics: how the market prices the announcement of a financial restatement; how financial restatements affect the announcing firm’s cost of capital and how financial restatements affect firms’ reputation. There are several issues to explore in future research, including whether financial restatements affect the dynamics of financial markets in Europe, whether the market fully and promptly assimilates the information content of a restatement, the role of financial analysts’ information disclosures in this process or how regulators may improve the way they provide investors with timely information about firms’ restating problems. Research limitations/implications: There is always some degree of subjectivity in the definition of the keywords, search strings and selection criteria in a systematic review. These are all important aspects, as they delimitate the scope of the study and define the sample of papers to be reviewed. Practical implications: The answers to the research questions identified in this paper may provide regulators with information to improve financial accounting and reporting standards and strengthen investors’ confidence in accounting information and the dynamics of financial markets. Originality/value: This paper systematically reviews the relevant literature exploring the connection between financial restatements and the dynamics of financial markets. It contributes to the academic community by identifying several research questions that may impact the theory and practice related to accounting quality and capital markets.